High yield from repeated testing for tuberculosis among high-risk citizens in Denmark - Nina Breinholt Staerke; Torben Smidt-Hansen; Leni Oldenborg; Torben Tranborg Jensen; Ulla Møller Weinreich; Shakil Shakar; Christian Wejse; Ole Hilberg; Andreas Fløe (International Journal of Infectious Diseases, 2021)
Background: Screening for TB (tuberculosis) among socially marginalized citizens has been implemented in many urban areas in countries with a low incidence of TB, including Denmark. This study aims to describe the findings of the screening programs for TB and latent tuberculosis (LTBI) used in the western part of Denmark in the period 2014–2019. Methods: Data was collected retrospectively on test results from interferon-gamma release assays (IGRA), spot sputum tests and chest X-rays performed as part of TB and LTBI screening among 1024 socially marginalized citizens in urban areas of western Denmark in 2014–2019. Results: The overall TB incidence was 2148/100.000 and number needed to screen to find one TB case was 39. The incidence of LTBI in the group screened using IGRA was 17.500/100.000. TB incidence when using spot sputum test was 2.5, while TB incidence when using IGRA as the primary screening test was 2.7. In total, 38.9% of TB diagnoses were obtained after the second or third round of screening. Conclusion: We demonstrated a high incidence of TB and LTBI among socially marginalized citizens in Denmark. Screening with spot sputum testing and IGRA generated comparable results in diagnosing TB in this setting.